1989
DOI: 10.1002/micr.1920100213
|View full text |Cite
|
Sign up to set email alerts
|

Complications from silicon‐polymer intubulation of nerves

Abstract: Three cases are reported to illustrate the potential danger of silicon-polymer intubulation of nerve for either nerve repair or following neurolysis. Since silicon-polymer intubulation of nerve is now a proven model for producing chronic nerve compression, its use clinically may be contraindicated where neural regeneration is the desired goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
152
1
9

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(162 citation statements)
references
References 21 publications
0
152
1
9
Order By: Relevance
“…16 De- spite Sunderland's pessimistic statement in 1978 that "the use of nonbiologic materials is of no value in the bridging of gaps in nerves," silicone tubes started being used in the 1980s as an effective alternative to end-to-end nerve coaptation in short segmental nerve loss. 8,19,30,34,42 However, the longer the nerve gap (range 2-5 cm), the poorer the functional recovery of sensory and motor skills in patients with either ulnar or median nerve transections repaired with silicone tubes, as reported by Braga-Silva. 6 The use of a tubular approach to repair peripheral nerve deficits in humans was based on findings from animal models, which showed that the lumen of a conduit formed an ideal biological environment for axonal growth.…”
Section: Discussionmentioning
confidence: 81%
“…16 De- spite Sunderland's pessimistic statement in 1978 that "the use of nonbiologic materials is of no value in the bridging of gaps in nerves," silicone tubes started being used in the 1980s as an effective alternative to end-to-end nerve coaptation in short segmental nerve loss. 8,19,30,34,42 However, the longer the nerve gap (range 2-5 cm), the poorer the functional recovery of sensory and motor skills in patients with either ulnar or median nerve transections repaired with silicone tubes, as reported by Braga-Silva. 6 The use of a tubular approach to repair peripheral nerve deficits in humans was based on findings from animal models, which showed that the lumen of a conduit formed an ideal biological environment for axonal growth.…”
Section: Discussionmentioning
confidence: 81%
“…Because of its inert and elastic properties, the silicon tube was one of the first and most frequently used to bridge the transected nerves (Azizi et al, 2010). Nevertheless, these non-biodegradable tubes induce fibrous capsule formation, leading to chronic nerve compression and an inflammatory response (Merle et al, 1989). In order to avoid problems associated with non-degradable guides, recent research has been focused on the production of biodegradable nerve guides (Ciardelli and Chiono 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Silicone was the choice of most authors in nerve entubulation research because it is relatively inert, nonreactive when in contact with the soft tissues and does not interfere with the regeneration process and secondary exploration of the repair site. Merle et al (10) were the first to use silicone nerve guides clinically, and reported successful nerve regeneration after reconstruction of peripheral nerves in three patients. Lundborg et al (3,4,11) presented several prospective studies on the clinical use of silicone conduits in which motor and sensorial recovery in ulnar and median nerves was excellent.…”
Section: Discussionmentioning
confidence: 99%